Predicting cardiovascular disease risk across the atherosclerotic disease continuum. (16th October 2020) - Poppe, Katrina K; Wells, Sue; Jackson, Rod; Doughty, Robert N; Kerr, Andrew J
Abstract: Aims: Cardiovascular disease (CVD) guidelines dichotomize populations into primary and secondary prevention. We sought to develop a risk equation for secondary prevention of CVD that complements existing equations for primary prevention of CVD, and to describe the distributions of CVD risk across the population. Methods and results: Adults aged 30–79 years who had routine CVD risk assessment in 2007–16 were identified from a large primary care cohort (PREDICT) with linkage to national and regional datasets. The 5-year risk of developing CVD among people without atherosclerotic CVD (ASCVD) was calculated using published equations (PREDICT-1°). A new risk equation (PREDICT-2°) was developed from Cox regression models to estimate the 5-year risk of CVD event recurrence among patients with known ASCVD. The outcome for both equations was hospitalization for a CVD event or cardiovascular death. Of the 475 161 patients, 12% (57 061) had ASCVD. For those without ASCVD, median (interquartile range) 5-year risks with the PREDICT-1° score were women 2.2% (1.2–4.2%), men 3.5% (2.0–6.6%), and whole group 2.9% (1.6–5.5%). For those with ASCVD, the 5-year risks with the new PREDICT-2° equation were women 21% (15–33%), men 23% (16–35%), and whole group 22% (16–34%). Conclusion: We developed CVD risk scores for people with ASCVD (PREDICT-2°) to complement the PREDICT-1° scores. Median CVD risk is eight-fold higher among those with ASCVD than those without; however, there was overlap and the widest distribution of CVD risk was among people with ASCVD. This study describes a CVD risk continuum and the limitations of a 'one size fits all' approach to assessing risk in people with ASCVD.